PENGARUH LEVERAGE TERHADAP AUDIT DELAY DENGAN MEDIASI CORPORATE GOVERNANCE PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI - Efata Indri Tarigan; Joan Yuliana Hutapea (Universitas Muhammadiyah Jember, 2020)
Mediation is used to compare the direct effect of capital between leverage onaudit delay and how the interaction between leverage when coupled with corporate governance mediation, changes to audit delay. Research purposes: every research that is done has the objective of doing the research. Being able to find out the effect of Leverage on Audit Delay with Corporate Governance asa mediating variable in companies listed on the Indonesia Stock Exchange for the period2018-2019 is the aim of this research. And also use process, path analysis and goodsmethod. This study uses a process and SPSS method Analytical techniques: descriptive analysis will be used in this research and then processedusing SPSS software, this study uses the coefficient of determination, significance t est, andregression analysis as statistical analysisSample and Variable: 20 BUMN companies listed on the Indonesia Stock Exchange for the 2018-2019 period were the samples for this study. This study uses leverage as thedependent variable and audit delay as the independent variable and corporate governanceas the mediating variable.Findings: The results of the analysis conducted in this study indicate that Leverage does not have a significant effect on Audit Delay, Corporate Governance has a significant e ffecton Audit Delay, and Leverage has no significant effect on Audit Delay with CorporateGovernance as a mediation.